Perencanaan Tata Letak Gudang Bahan Baku Menggunakan Metode Dedicated Storage pada PT. Bonecom Tricom - Teddy Arianto; Heru Darmawan; Rani Rahmadiyani (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This research aims to redesign the design of raw material storage rooms to improve efficiency in material storage and retrieval at PT. Bonecom Tricom. The problems found include limited storage space capacity for raw materials which causes the utilization of warehouse areas to be less than optimal, storage layouts that have not been effectively organized so as to hinder the process of finding and retrieving materials, and the use of forklifts that interfere with the smooth flow of materials. This condition results in an increase in material transfer distance, longer handling time, and decreased warehouse operational efficiency. The method applied in this study is descriptive, with data collection techniques through direct observation, interviews, and secondary data documentation studies. The data collected includes the arrangement of existing facilities, the distance between work areas, the movement of raw materials, and the size and location of each facility. In the layout redesign, the Fixed Storage method was applied, which was based on the analysis of the throughput ratio as well as the space requirements for each product. At the end of this study, it is hoped that it can provide suggestions for improvements to the layout system that will optimize the use of space and smooth the flow of materials in the warehouse.